In situ and Ex situ Catalytic Pyrolysis of Microalgae and Integration With Pyrolytic Fractionation - Shirazi, Yaser; Viamajala, Sridhar; Varanasi, Sasidhar (Frontiers in Chemistry, 2020)
Microalgae are attractive feedstocks for biofuel production and are especially suitable for thermochemical conversion due to the presence of thermally labile biomass constituents -lipids, starch and protein. However, the thermal degradation of starch and proteins produces water as well as other O-and N-compounds that are mixed-in with energy-dense lipid pyrolysis products. To produce hydrocarbon-rich products from microalgae biomass, we assessed in situ and ex situ catalytic pyrolysis of a lipid-rich Chlorella sp. in the presence of the HZSM-5 zeolite catalyst over a temperature range of 450-550 °C. Results show that product yields and compositions were similar under both in situ and ex situ conditions with aromatics produced as the primary products. Yields of aromatics increased with increasing temperature and the highest aromatic yield and selectivity was obtained at 550 °C. Also, at this temperature, oxygenates and nitrogenous compounds were not detected among the liquid products during ex situ catalytic pyrolysis. We also assessed the feasibility of a two-step fractional pyrolysis approach integrated with vapor phase catalytic upgrading. In these experiments, the biomass was first pyrolyzed at 320 °C to volatilize and degrade starch and protein. Then, the residual biomass was pyrolyzed again at 450 °C to recover products from lipid decomposition.The volatiles from each fraction were passed through an ex situ catalyst bed. Results showed that net product yields from the 2-step process were similar to the single step ex situ catalytic pyrolysis at 450 °C indicating that tailored vapor phase upgrading can be applied to allow separate recovery of products from the chemically distinct biomass components -(1) lower calorific value starch and proteins and (2) energy-dense lipids.